Acute Effects of Whole-Body Vibration on Dopplerfluxometry of the Common Carotid Artery Parameters among Adult and Elderly Non-Athletes Healthy Dogs - Nagai, Lais Rosa; Rahal, Sheila Canevese; Dadalto, Carmel; da Silva, Bruna Martins; Tsunemi, Miriam; Mamprim, Maria Jaqueline; Gallina, Marina Frazatti; Nagamo, Ygor Faria; Lopes, Stella Helena Sakata; dos Santos, Ivan Felismino Charas (Acta Scientiae Veterinariae, 2020)
Background: Whole-Body Vibration (WBV) is an oscillatory mechanical stimulus spreading throughout the body and considered a type of physical exercise because of the activation of the cardiovascular, musculoskeletal, and neuroendocrine systems. It is a physical exercise modality since it promotes cardiovascular resistance, increase in muscular strength and neurosensitivity, and motor coordination improvement. For use of WBV as an exercise modality for dogs, it is necessary to evaluate the Dopplerfluxometry parameters of the common carotid artery in healthy dogs in order to perform a safe protocol without inducing any cerebral alteration. This study aimed to evaluate the acute effects of WBV on systolic peak velocity (SPV), resistivity (RI), and pulsatility index (PI) of the both common carotid artery among adults and elderly non-athletes healthy dog. Materials, Methods & Results: Fourteen clinically healthy, neutered crossbreed male dogs, non-athlete were divided into two groups of seven dogs, according to the age group: Group 1 (G1)- Adult dogs: age between 12 and 84 months; Group 2 (G2)- Elderly dogs: aged over 84 months. All dogs were submitted to sessions of WBV using the protocol of 30 Hz for 5 min, followed by an increase to 50 Hz for 5 more min and ending with 5 min at 30 Hz, without rest between the variation of the vibration frequency. The systolic peak velocity (SPV), resistivity (RI), and pulsatility index (PI) of the common carotid artery were assessed in two time-points: 5 min before the WBV sessions (5PRE) and 1 min after the WBV (1POS). No significant variations in the SPS, RI, and PI of both common carotid artery of the G1 and G2 were identified. The anatomic reference for the left and right common carotid artery was the right and left extern jugulars veins, which were identified by the venous blood vessel characteristics as endothelium type, and single-phase without systolic peaks wave. Discussion: In humans, WBV is indicated to muscle size and tone increase, therefore it is believed that this modality can present a beneficial result in dogs with muscular atrophy associated with orthopedic surgeries and in cases of osteoarthritis. Irreversible brain damage can be caused by a possible hemodynamic alteration in the common carotid arteries resulted from mechanical vibrations. Parkinson’s disease patients and individuals affected by strokes that went under acute sessions of WBV showed handshake reduction and better proprioception, respectively. The beneficial effect was observed in cervix opening in dogs with metritis. The behavior of sitting of the dogs over 30 kg during WBVsessions was associated with paraparesis. This result was present in medium-size non-athletic dogs weighing from 10.1 to 17.9 kg that went through WBV for 5 consecutive days, using the same vibrating platform. No signs of discomfort during a single session of 10 min of WBV (15 and 21 Hz) were observed in healthy adult horses. Studies using mechanical vibrations on adult healthy dogs did not show significant variation RI of the renal artery. On the other hand, daily use of WBV for 5 days on dogs showed significant enhancement on RI of the femoral artery immediately after it. A single session of WBV (30 and 50 Hz did, for 15 min) do not produce undesirable effects on SPV, RI, and PI of both common carotid arteries in adult and elderly non-athletic healthy dogs.